PENGARUH PERSEPSI SERTIFIKASI HALAL, KUALITAS PRODUK, DAN HARGA TERHADAP PERSEPSI PENINGKATAN PENJUALAN - AHDA SEGATI (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aimed to find out about the effect of halal certificate, product quality, and price on sales increase in Aqiqah Catering Nurul Hayat Yogyakarta.This was a field research which used quantitative approach. The population was all the consumers and producers of Aqiqah Catering Nurul Hayat Yogyakarta. The sample was selected using sample random sampling with a total of 150 respondents. The method used in this study was quantitative with multiple linear regressions. The findings showed that the variables of halal certificate, product quality, and price have a significant effect on sales increase. This is evident from the Fcount of 8.151 > Ftable of 2.67 with a significance of 0.000 (> 0.05). Therefore, H0 was rejected and H1 was accepted, meaning that there is a simultaneous effect of the variables of halal certificate, product quality, and price have a significant effect on sales increase in Aqiqah Catering Nurul Hayat Yogyakarta. In addition, the variables of halal certificate, product quality, and price have a significant effect on sales increase of 12.6%, evident from the R2 of 0.126, while the remaining 87.4% is affected by other variables not discussed in this model.